Engaging Indigenous Economy. Debating diverse approaches - Sanders, Will (ANU Press, 2016)
The engagement of Indigenous Australians in economic activity is a matter of long-standing public concern and debate. Jon Altman has been intellectually engaged with Indigenous economic activity for almost 40 years, most prominently through his elaboration of the concept of the hybrid economy, and most recently through his sustained and trenchant critique of policy. He has inspired others also to engage with these important issues, both through his writing and through his position as the foundation Director of The Australian National University's Centre for Aboriginal Economic Policy research from 1990 to 2010. The year 2014 saw both Jon's 60th birthday and his retirement from CAEPR. This collection of essays marks those events. Contributors include long‑standing colleagues from the disciplines of economics, anthropology and political science, and younger scholars who have been inspired by Jon's approach in developing their own research projects. All point to the complexity as well as the importance of engaging with Indigenous economic activity - conceptually, empirically and as a strategic concern for public policy.